Eight Times Contemporary Indigenous Art – 8 x AIC (Palíndromo, 2023)
Based on the concept of Contemporary Indigenous Art – AIC – enunciated by Jaider Esbell (2016, 2018a; 2018b), we present a brief collection involving eleven works by eight artists: Arissana Pataxó, Carmézia Emiliano, Denilson Baniwa, Daiara Tukano, Ibã Huni Kuin (MAHKU Collective), Jaider Esbell, Joseca Yanomami and Mário Flores Taurepang. Where a singular aesthetic is enunciated, a logic of the Amerindian sensation, images that bravely resisted colonization. Ancestral images that tell us about one in a little while. The essay seeks to expose an initial landscape of Contemporary Indigenous Art, a movement that is in full swing. The theoretical framework used comes from Amerindian thought and the philosophy of difference.
Keywords: Contemporary Indigenous Art; Jaider Esbell; Image